Identification and Prioritization of Key Performance Indicators for the Construction Small and Medium Enterprises - Okudan, Ozan; Budayan, Cenk; Arayici, Yusuf (TURKISH CHAMBER CIVIL ENGINEERS, 2022)
Purpose: The central purpose of this study is to propose a set of key performance indicators (KPIs) to measure the performance of construction small and medium enterprises (SMEs) that have been ignored in the performance management literature so far. Secondly, this study aims to determine the most crucial KPIs by using the fuzzy VIKOR method to improve cost-effectiveness in the performance measurement of construction SMEs. At the first stage of this study, KPIs proposed by the existing studies were identified via a literature survey. Then, the KPIs extracted from the literature survey were verified, and eight new KPIs were proposed as a result of focus group discussions with 12 participants who are owners/managers of construction SMEs. Additionally, the Balanced Scorecard (BSC) was modified in line with the needs of construction SMEs, and each KPI was grouped into a B SC perspective. A questionnaire survey followed this grouping to gather data associated with the KPIs. Based on these data, KPIs were prioritized by using the fuzzy VIKOR. It is found out that external indicators such as effectiveness of monitoring market conditions are determined as the most important KPIs, in contrast to the findings in the studies about large-scale companies. Furthermore, Attracting new customers; Reliability of financial performance and, Competency of managers are identified as important indicators. Four KPIs proposed by experts during the focus group discussion are placed among the most important KPIs, which highlights the need for a specific performance measurement system (PMS) for construction SMEs.
Keywords: Performance measurement; KPIs; construction SMEs; fuzzy VIKOR; MCDM; WORKING CAPITAL MANAGEMENT; BALANCED SCORECARD; MEASUREMENT SYSTEM; SUCCESS FACTORS; SMES; BUSINESS; PERSPECTIVE; RESPONSES; CRISIS; Engineering